Motivating Bureaucrats through Social Recognition : Evidence from Simultaneous Field Experiments - Gauri, Varun; Jamison, Julian C.; Mazar, Nina; Ozier, Owen; Raha, Shomikho; Saleh, Karima (World Bank, Washington, DC, 2018)
Bureaucratic performance is a crucial determinant of economic growth. Little is known about how to improve it in resource-constrained settings. This study describes a field trial of a social recognition intervention to improve record keeping in clinics in two Nigerian states, replicating the intervention -- implemented by a single organization -- on bureaucrats performing identical tasks in both states. Social recognition improved performance in one state but had no effect in the other, highlighting both the potential and the limitations of behavioral interventions. Differences in observables did not explain cross-state differences in impacts, however, illustrating the limitations of observable-based approaches to external validity.